Sall4 and Myocd Empower Direct Cardiac Reprogramming From Adult Cardiac Fibroblasts After Injury - Zhao, Hong; Zhang, Yi; Xu, Xiaochan; Sun, Qiushi; Yang, Chunyan; Wang, Hao; Yang, Junbo; Yang, Yang; Yang, Xiaochun; Liu, Yi; Zhao, Yang (Frontiers in Cell and Developmental Biology, 2021)
Direct conversion of fibroblasts into induced cardiomyocytes (iCMs) holds promising potential to generate functional cardiomyocytes for drug development and clinical applications, especially for direct in situ heart regeneration by delivery of reprogramming genes into adult cardiac myofibroblasts in injured hearts. For a decade, many cocktails of transcription factors have been developed to generate iCMs from fibroblasts of different tissues in vitro and some were applied in vivo. Here, we aimed to develop genetic cocktails that induce cardiac reprogramming directly in cultured adult cardiac myofibroblasts isolated from infarcted mice, which could be more relevant to heart diseases. We found that the widely used genetic cocktail, Gata4, Mef2c, and Tbx5 (GMT) were inefficient in inducing iCMs from adult cardiac myofibroblasts. In a whole well of a 12-well plate, no more than 10 mCherry+ cells were observed after two weeks of GMT infection with Myh6-reporter transgenic myofibroblasts. By screening 22 candidate transcription factors predicted through analyzing the gene regulatory network of cardiac development, we found that five factors, GMTMS (GMT plus Myocd and Sall4), induced more iCMs expressing the cardiac structural proteins cTnT and cTnI at a frequency of about 22.5 ± 2.7% of the transduced MICFs at day 21 post infection. What is more, GMTMS induced abundant beating cardiomyocytes at day 28 post infection. Specifically, Myocd contributed mainly to inducing the expression of cardiac proteins, while Sall4 accounted for the induction of functional properties, such as contractility. RNA-seq analysis of the iCMs at day 28 post infection revealed that they were reprogrammed to adopt a cardiomyocyte-like gene expression profile. Overall, we showed that Sall4 and Myocd play important roles in cardiac reprogramming from adult cardiac myofibroblasts, providing a cocktail of genetic factors that have potential for further applications in in vivo cardiac reprogramming.